(untitled) (Journal of Asian Development Studies, 2023)
This study investigates the impact of ethnic, religious, and socioeconomic conditions on the exchange rate in selected South Asian countries. The specific factors have a positive and negative effect on the exchange rates of the projected countries. The data nature is a panel; the period is 1984–2017. The econometric technique of the cross-sectional auto-regression distributed lag model (CS-ARDL) was used. Ethnic tension, religious tension, socioeconomic conditions, law and order, and political stability significantly influence exchange rate. Ethnic and religious tensions have negative impacts on exchange rate. As well, law & order and political stability have a positive effect on the exchange rate in the context of Pakistan. The study suggests that the projected nations focus on long-term policies, invest in social and economic development, enhance their legal systems and political reforms, and mitigate short-term risk and conflict.